Does Location Still Matter? The Dominance of Islamic Ethics and Service Quality in Muslim Fashion Retail Satisfaction - Syakia Ramadhani; Melis; Citra Lestari (CV. Era Digital Nusantara, 2025)
This quantitative research aims to analyze the influence of Islamic Business Ethics, Location, and Service Quality on Consumer Satisfaction at Rabbani Lahat Store. The study population comprised 16,160 consumers, with a sample of 100 people determined using the Slovin formula. The data were analyzed using Multiple Regression (SPSS) through the t-test and F-test. The results indicate that, partially, Islamic Business Ethics and Service Quality significantly influence consumer satisfaction, while the Location variable does not show a significant effect. However, simultaneously (together), these three variables—Islamic Business Ethics, Location, and Service Quality—exert a significant combined influence on consumer satisfaction at Rabbani Lahat Store. The main conclusion of this study is that consumer satisfaction at Rabbani Lahat is highly driven by Sharia ethical values ​​in business and the quality of service provided, while the physical location of the store is less of a primary determinant.